On the Security of Data Collection and Transmission from Wireless Sensor Networks in the Context of Internet of Things - Hong Yu; Jingsha He; Ruohong Liu; Dajie Ji (International Journal of Distributed Sensor Networks)
In the context of Internet of Things (IoT), multiple cooperative nodes in wireless sensor networks (WSNs) can be used to monitor an event, jointly generate a report and then send it to one or more Internet nodes for further processing. A primary security requirement in such applications is that every event data report be authenticated to intended Internet users and effectively filtered on its way to the Internet users to realize the security of data collection and transmission from the WSN. However, most present schemes developed for WSNs don't consider the Internet scenario while traditional mechanisms developed for the Internet are not suitable due to the resource constraint of sensor nodes. In this paper, we propose a scheme, which we refer to as Data Authentication and En-route Filtering (DAEF), for WSNs in the context of IoT. In DAEF, signature shares are generated and distributed based on verifiable secret sharing cryptography and an efficient ID-based signature algorithm. Our security analysis shows that DAEF can defend against node compromise attacks as well as denial of service (DoS) attacks in the form of report disruption and selective forwarding. We also analyze energy consumption to show the advantages of DAEF over some comparable schemes.